Global politics and violent non-state actors - Ezrow, Natasha M. (Thousand Oaks, CA : Sage Pub., 2017)
Moving beyond terror groups to examine non-state actors including warlords, gangs and private security companies, Violent Non-State Actors:, Guides you through the core theories and concepts, taking a multidisciplinary approach, Examines different explanations for the emergence of violent non-state actors as well as strategies for dealing with them, Weaves in international case studies from groups including the Islamic State, Los Zetas, Hamas, and Al Qaeda, as well as discussion questions, further reading and definitions of key terms A must read for upper-level undergraduate and postgraduate students in politics, international relations, security and terrorism studies.
Description based on MARC record for print version.
Keywords: Non-state actors (International relations).; Political violence; Terrorism